Role of radiotherapy and chemotherapy in the treatment of lymphomas - Ramot, B. (1979)
The recent developments and results of treatment in Hodgkin's disease suggest that staging laparotomy is indicated in certain selected groups of patients and should not be performed routinely in patients whose therapy is unlikely to be changed by the findings. Early stage nodal Hodgkin's disease is best treated by extended radiotherapy. The exact role of adjuvant chemotherapy is not settled, but there are certain groups of high-risk patients who should receive chemotherapy, such as those with extensive mediastinal disease or advanced IIIA patients. In the advanced stages, chemotherapy assumes the primary role and with the MOPP programme (chlormethine, vincristine, procarbazine, and prednisone), alone or alternating with ABVD (doxorubicin, bleomycin, vinblastine, and imidazole carboxamide), a substantial number of patients can be controlled or cured. The therapeutic approach to non-Hodgkin's lymphoma should be guided mainly by the histological findings, favourable or unfavourable, and to a lesser degree also by the stage of the disease. In these patients, chemotherapy rather than radiotherapy is the treatment of choice. In the favourable histology group, a conservative approach is usually justified in the majority of patients, while in the unfavourable histology group, aggressive combination chemotherapy containing adriamycin is the recommended therapy. In underprivileged populations, the abdominal and intestinal localization of lymphomas is more common than in Europe and North America. Two lymphomas of special interest are Burkitt's lymphoma and intestinal lymphoma in their varying aspects. In both diseases, the importance of environmental factors is highly suggestive. Referral of such patients to centres involved in the management of these diseases is essential.